The crystal structure of 4-(3-carboxy-1-ethyl-6-fluoro-4-oxo-1,4-dihydroquinolin-7-yl)piperazin-1-ium 2-carboxy-6-nitrobenzoate monohydrate, C24H25FN4O10 - Sun Yu-Yun; Gu Zhan-Ning; Jiang Cheng-Jun (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C24H25FN4O10, triclinic, P1̄ (no. 2), a = 7.7217(3) Å, b = 9.9451(4) Å, c = 15.9291(6) Å, α = 101.741(1)∘, β = 98.762(1)∘, γ = 96.148(1)∘, V = 1171.56(8) Å3, Z = 2, Rgt(F) = 0.0389, wRref(F2) = 0.1162, T = 170 K.